Human papillomavirus type 16 antagonizes IRF6 regulation of IL-1β. - Michelle Ainouze (PLoS Pathogens, 2018)
Human papillomavirus type 16 (HPV16) and other oncoviruses have been shown to block innate immune responses and to persist in the host. However, to avoid viral persistence, the immune response attempts to clear the infection. IL-1β is a powerful cytokine produced when viral motifs are sensed by innate receptors that are members of the inflammasome family. Whether oncoviruses such as HPV16 can activate the inflammasome pathway remains unknown. Here, we show that infection of human keratinocytes with HPV16 induced the secretion of IL-1β. Yet, upon expression of the viral early genes, IL-1β transcription was blocked. We went on to show that expression of the viral oncoprotein E6 in human keratinocytes inhibited IRF6 transcription which we revealed regulated IL-1β promoter activity. Preventing E6 expression using siRNA, or using E6 mutants that prevented degradation of p53, showed that p53 regulated IRF6 transcription. HPV16 abrogation of p53 binding to the IRF6 promoter was shown by ChIP in tissues from patients with cervical cancer. Thus E6 inhibition of IRF6 is an escape strategy used by HPV16 to block the production IL-1β. Our findings reveal a struggle between oncoviral persistence and host immunity; which is centered on IL-1β regulation.